Identifikasi Kemampuan Berpikir Kreatif Dalam Penggunaan Aplikasi Canva Untuk Siswa SD - Kalysa Nenotek; Kintan Limiansih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify elementary school students creative thinking skills in using the Canva digital application. The background of this research lies in the importance of developing creative thinking skills in 21st-century learning, as well as the implementation of the Merdeka Curriculum which emphasizes the Pancasila Student Profile dimensions, one of which is creative thinking. This research employed a qualitative approach with data collection conducted through interviews with four sixth-grade students at an elementary school in Yogyakarta. Data analysis followed the interactive model of Miles and Huberman, involving data collection, data reduction, data presentation, and drawing conclusions. The results indicate that the four indicators of creative thinking—fluency, flexibility, originality, and elaboration—are present among the students. The students demonstrated the ability to generate ideas using Canva templates, develop and modify initial designs, create unique designs relevant to the subject matter, and explain their design processes, although some students still faced issues with self-confidence. The use of Canva proved to be an effective medium for enhancing students’ creative thinking abilities and promoting innovation and exploration in learning activities. This study recommends the use of Canva as a supportive educational tool to foster students' creative and digital competencies.